dane są dwa wyrażeia: A=2k+2 i B=2-2k. Które z poniższych wyrażeń jest równe iloczynowi A*B?
A. (A-B)*k+4 B. (B-A)*k+4 C. (A+B)*k+2 D. (A+B)*k^2-2


Odpowiedź :

Odpowiedź:

A = 2k + 2 ; B = 2 - 2k

A * B = (2k + 2)(2 - 2k) = (2 + 2k)(2 - 2k) = 4 - 4k²

(A - B) * k + 4 = (2k + 2 - 2 + 2k) * k + 4 = 4k * k + 4 = 4k² + 4

(B - A) * k + 4 = (2 - 2k - 2k - 2) * k + 4 = - 4k * k + 4 = - 4k² + 4 = 4 - 4k²

(A + B) * k + 2 = (2k + 2 + 2 - 2k) * k + 2 = 4k + 2

(A + B) * k² - 2 = (2k + 2 + 2 - 2k) * k² - 2 = 4k² - 2

Odp: B